A load spectrum editing method of time-frequency for rubber isolators based on the continuous wavelet transform. (July 2022) - Liu, Xiangnan; Zhao, Xuezhi; Liu, Xiao-Ang; Shangguan, Wen-Bin
Highlights: The load spectrum editing method of rubber isolator under the criterion of real damage retention is studied. A time-frequency editing method based on the continuous Morlet wavelet transform is proposed. The fatigue damage of the powertrain mount is analyzed numerically. Abstract: The load spectrum editing method of rubber isolator under the criterion of real damage retention was studied. A time-frequency editing method based on the continuous Morlet wavelet transform (CMWT) was proposed. In this method, the accumulative power spectral density (APSD) of strain-load spectrum was obtained using the CMWT method. Then an APSD threshold was set and time segments with small damage contribution in the load spectrum were identified and removed to obtain the edited load spectrum. For comparisons, the conventional time-domain editing method was used to edit the load spectrum. The obtained results show that the time compression of the proposed method is larger than that of the other editing method. The original and edited load spectra are consistent in terms of statistical parameters. Moreover, based on the mount fatigue analysis, the edited load spectrum was verified to have the same loading effect as the original load spectrum.